A PROSPECTIVE STUDY OF COMPARISION OF HORMONAL V/S NON-HORMONAL TREATMENT IN ABNORMAL UTERINE BLEEDING - SONAM; MAHESWARI, SUNITA; SHARMA, RAJRANJ; GILL, GURKIRAN (International Journal of Current Pharmaceutical Research, 2023)
Objective: Abnormal Uterine Bleeding (AUB) is a common problem among women in the reproductive age group. It can be characterized by variations in duration, frequency, regularity of menses, or volume of menstrual blood loss. AUB can have a significant impact on quality of life, causing pain, discomfort, social embarrassment, and loss of productivity. It may require surgical interventions, including hysterectomy. Hormonal and non-hormonal treatments are available options for managing AUB. Methods: This study aimed to compare the effectiveness of hormonal and non-hormonal treatments in abnormal uterine bleeding. The research question addressed in this study was: "Which treatment is better, hormonal or non-hormonal, in abnormal uterine bleeding?" Results: The study findings provided insights into the comparative efficacy of hormonal and non-hormonal treatment options for abnormal uterine bleeding. The results contributed to understanding the optimal approach for managing this condition and improving patient outcomes. Conclusion: Based on the results of this study, conclusions can be drawn regarding the superiority of either hormonal or non-hormonal treatment in the management of abnormal uterine bleeding. The findings will help guide healthcare professionals in selecting appropriate treatment options for their patients.